Analisis Hukum Keluarga Islam Terhadap Perceraian Akibat Perselingkuhan Di Media Sosial - Agung Pramudita Pramudita; Rohmat; Syeh Sarip Hadaiyatullah (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2026)
Marriage is a physical and spiritual bond that aims to form a family based on sakinah, mawaddah, and rahmah in accordance with Law No. 1 of 1974. However, the phenomenon of infidelity on social media (cyber infidelity) has increased along with the development of digital technology, causing emotional closeness with a third party outside of the marriage bond. The impact is in the form of ongoing disputes, loss of trust, and separation, which disrupts household harmony. Previous studies have highlighted the social and psychological impacts of cyber infidelity, but normative juridical studies from the perspective of Islamic Family Law are still limited. The research questions in this study are how the judge assessed this behavior in the Probolinggo Religious Court Decision Number 140/Pdt.G/2025/PA.Prob and how Islamic family law analyzes divorce due to social media infidelity. This study uses a normative-analytical method based on library research, examining legal literature, the Qur'an, KHI, PP No. 9 of 1975, and court decisions. The results of the study show that cyber infidelity is a violation of marital obligations that damages loyalty, 'iffah, and trust, and can be classified as nusyuz if it causes continuous disputes. The panel of judges considers this behavior a substantial factor in broken marriages, so that divorce can be granted legally according to Islamic law and regulations, in order to maintain justice, benefit, and the rights of all parties involved.